Preparation and Property of Hydroxyapatite/Poly(methyl methacrylate) Composites by in situ Copolymerization - Yang, Benhong; Li, Meng; Wu, Yun; Wang, Fei (Asian Journal of Chemistry, 2013)
Modified hydroxyapatite (m-HA) nanoparticles were synthesized via the hydrothermal method and followed by modification with a ilane coupling agent. Hydroxyapatite/poly(methyl methacrylate) composites were prepared using the in situ copolymerization of methyl methacrylate and modified hydroxyapatite particles. SEM images revealed that modified hydroxyapatite particles dispersed homogeneously in poly(methyl methacrylate) matrix when its content was lower than 1.0 wt % due to the covalent interaction between modified hydroxyapatite and poly(methyl methacrylate), but tended to aggregate at higher contents. Results show that the incorporation of modified hydroxyapatite could improve thermal and mechanical properties of poly(methyl methacrylate).